Pemanfaatan Benteng Tundakan Sebagai Sumber Belajar Sejarah di SMAN 1 Paringin - Muhammad Akbar Setyawan; Rochgiyanti, Rochgiyanti; Susanto, Heri (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to analyse the use of Tundakan Fort as a history learning resource at SMAN 1 Paringin. The method used in the research used a qualitative approach. Data sources were obtained through observation, interviews, and documentation. As for data analysis, it refers to Miles and Huberman which consists of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the utilisation of Tundakan Fort as a history learning resource at SMAN 1 Paringin had a positive impact on students' understanding of local history and increased their sense of concern for the preservation of cultural heritage. In the utilisation of Tundakan Fort as a source of history, the teacher directed students to conduct interviews with several residents of Tundakan Village. Furthermore, students were taken to the Tundakan Fort area to make observations and documentation. Then the form of evaluation used is by doing group assignments to students. This activity was carried out with the aim of measuring students' understanding of history through the results of students' observations and analyses of the Tundukan Fort. The obstacles faced include transportation, time constraints, the difficulty of coordinating students in the field and coordinating students outside of school hours.